Enhancing Employee Performance Using Workgroup Effectiveness: Role of Member Trust - Wanuri; Khayatun, Siti; Hartarini, Yovita Mumpuni (Universitas Negeri Semarang, 2024)
Research aims to offer comprehensive understanding of the factors influencing organizational performance, particularly in the context of member trust, thereby contributing to broader discourse on human capital management and cooperative development. Utilizing multidimensional framework of human capital and grounded in prevailing challenges faced by cooperative businesses, research elucidates pivotal role of human capital as organizational performance. Approach research was based on descriptive research techniques, in cross-sectional survey, is to observe (collect data about) specific occurrence, often at single point in time. To address research questions, this study adopts descriptive research technique and survey measures to capture objective and social reality of employee performance. Sample included 140 respondents of Flower Market Traders Association in Kopeng, Semarang district, Central Java Province. Data gathering period lasted from January until October 2023. Researcher created questionnaire and collected data using Google Forms. Data analysis was conducted using Structural Equation Modeling (SEM) with Smart-PLS (Partial Least Square) software. Based on study's results, workgroup effectiveness directly influences employee performance and contributes to its success. Moreover, member trust as moderator in correlation between workgroup effectiveness and employee performance. Research offers theoretical and practical implications for implementing workgroup effectiveness to enhance employee performance and member trust as moderator.